2019
DOI: 10.1002/dmrr.3201
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐specific characteristics of atherosclerotic plaques in femoral arteries determined by three‐dimensional magnetic resonance vessel wall imaging

Abstract: ObjectivesThis study aimed to investigate the characteristics of femoral atherosclerotic plaques in patients with diabetes mellitus (DM) compared with those without DM using three‐dimensional magnetic resonance vessel wall imaging.MethodsLower extremity atherosclerotic disease patients with and without DM (age ≥ 50 year‐old) were recruited and underwent three‐dimensional magnetic resonance imaging for femoral arteries. The femoral arteries were divided into common femoral artery (CFA), proximal of superficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Gao et al 30 reported neovascularization was more frequent in the coronary atherosclerotic lesions of patients with DM using optical coherence tomography. Han et al 31 recently demonstrated more IPH presence in femoral arteries of DM patients using vessel wall imaging. In the present study, we found a significantly higher incidence of IPH in patients with diabetes, especially those with poor glycemic control.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gao et al 30 reported neovascularization was more frequent in the coronary atherosclerotic lesions of patients with DM using optical coherence tomography. Han et al 31 recently demonstrated more IPH presence in femoral arteries of DM patients using vessel wall imaging. In the present study, we found a significantly higher incidence of IPH in patients with diabetes, especially those with poor glycemic control.…”
Section: Discussionmentioning
confidence: 98%
“…Gao et al 30 reported neovascularization was more frequent in the coronary atherosclerotic lesions of patients with DM using optical coherence tomography. Han et al 31 recently demonstrated more IPH presence in femoral arteries of DM patients using vessel wall imaging.…”
Section: Discussionmentioning
confidence: 98%
“…Arterial narrowing in the adductor canal and arterial encapsulation inside this muscular aponeurotic canal have been identified as factors predisposing to plaques in this area. 36 However, there is no explanation for the fact that diabetics exhibit different behavior in this sector.…”
Section: Discussionmentioning
confidence: 99%
“…No escore de Bollinger et al, também houve predomínio de lesões nas artérias femoral profunda, femoral superficial e poplíteas entre os não diabéticos. O estreitamento arterial no canal dos adutores e o encapsulamento arterial dentro desse canal musculoaponeurótico são apontados como fatores de favorecimento de placas nesse local 36 . No entanto, não há explicação para o fato de os diabéticos terem comportamento diferente nesse setor.…”
Section: Discussionunclassified
“…In addition, another study by Thiruvoipati et al also showed that diabetes was associated with greater severity of cardiovascular disease and worse clinical outcomes compared to nondiabetics [16]. Diabetes may promote in ammation in ltration and larger LRNC formation in carotid plaques, leading to plaque rupture and larger emboli formation [17], which will be more likely to result in a subsequent ischemic stroke rather than a TIA.…”
Section: Discussionmentioning
confidence: 99%